2022
DOI: 10.3390/separations9040087
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Flavanol-Rich Nutraceuticals Based on High-Performance Liquid Chromatography

Abstract: Flavanols are a class of polyphenols that have become the focus of much research because of their medicinal properties. For this paper, a new method to determine polyphenols in nutraceutical samples was developed, based on solid-liquid extraction and further analysis by liquid chromatography. Analytes were recovered by ultrasound-assisted extraction, using a mixture of methanol/water/hydrochloric acid (70:29:1, v:v:v) as the solvent. Reversed-phase high-performance liquid chromatography with ultraviolet/visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Some limitations include the exclusion of date restrictions when conducting the search and thus some data that met the inclusion criteria were analysed using methods that are currently not considered good quality. The Folin-Ciocalteu method has been critiqued as it lacks specificity for phenolic compounds and is known to overestimate values when other reducing agents are also present in the foods, compared to the more specific high-performance liquid chromatography (HPLC) methods [55]. Nonetheless, as this was the first stage in the process leading to the development of a national polyphenol database and in the absence of any prior knowledge of the extent of data available, it was deemed important to obtain as much data as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations include the exclusion of date restrictions when conducting the search and thus some data that met the inclusion criteria were analysed using methods that are currently not considered good quality. The Folin-Ciocalteu method has been critiqued as it lacks specificity for phenolic compounds and is known to overestimate values when other reducing agents are also present in the foods, compared to the more specific high-performance liquid chromatography (HPLC) methods [55]. Nonetheless, as this was the first stage in the process leading to the development of a national polyphenol database and in the absence of any prior knowledge of the extent of data available, it was deemed important to obtain as much data as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were taken at different intervals over 24 h, diffused through a syringe Millipore filter (0.4 µm), and evaluated using HPLC at a λ max of 280 nm, based on Casanella et al’s method [ 34 ]. The amount of CBPE permeated was calculated by measuring the surface area of the intestinal sac, which was modeled as a cylinder [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the method had high precision (%RSD 0.2 to 1.9%) and accuracy (100.7 to 102.9%) and was successfully used to evaluate flavanols and proanthocyanidins in different cocoa products. Vidal-Casanella et al [131] developed a reversed-phase high-performance liquid chromatography method with HPLC-UV/Vis and FLD to determine the content of major flavanols. The results showed that the HPLC-FLD method has better selectivity and sensitivity, and the detection limit is 0.1 mg L −1 .…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%